PENERAPAN ALGORITMA LINEAR REGRESI PADA SMART APLIKASI E-RESORT MENGGUNAKAN FRAMEWORK CODEIGNITER - Sasmita Sasmita; Buhori Muslim (JITEK (Jurnal Ilmiah Teknosains), 2022)
The purpose of this study is to apply linear regression algorithm to smart e-resort applications using a codeigniter framework so that it can run effectively and efficiently. Hotel Pagar Alam is currently still using manual methods, such as distributing brochures, this of course hinders the activities of hotels which are usually crowded and crowded on holidays or other major holidays that require hotels as a means to stay overnight, systems that can speed up the work of the manager and make it easier visitors to access reservation information as well as hotel facilities. By using the system development method Software Defelopment Life Cycle (SDLC) method. This smart e-resort was created using the PHP programming language with the Codeigniter framework and MySQL as the database. Testing of this system uses Black Box Testing with a score of 3.5 and expert review with a score of 4.1 from the implementation of Betha recapitulation in the valid category. Thus the application of the linear regression algorithm in the smart e-resort application using a codeigniter framework can run validly and efficiently